On the conditions of 'late urbanisation'. (August 2022) - Fox, Sean; Goodfellow, Tom
We are living through a global urban transition, but the timing of this transition has varied significantly across countries and regions. This geographic variation in timing matters, both theoretically and substantively. Yet contemporary debates on urbanism hinge primarily on questions of universalism versus particularism, at the expense of attention to how history and geography collide to shape urban processes. Specifically, they neglect the critical fact that urbanisation in many countries today is late within the context of the global urban transition. We argue that trajectories of contemporary urbanisation must be understood in relation to a suite of conditions unique to the late 20th and early 21st centuries and partly shaped by early urbanisation, including historically unprecedented demographic intensity, hyperglobalisation, centripetal state politics and the spectre of environmental catastrophe in the late Anthropocene. These factors condition the range of possibilities for late urbanisers in ways that did not apply to early urbanisers yet can also produce diverse outcomes depending on local circumstances. We draw on a comparison between countries in sub-Saharan Africa and China to illustrate why the conditions of late urbanisation matter, but also why they have produced highly variable outcomes and are not deterministic of urban futures.